2021
DOI: 10.1088/1755-1315/926/1/012102
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Addition of Bagasse Ash and Eggshell Powder on CBR Value of Clay Soil

Abstract: In the construction of road construction, soil bearing capacity, such as the CBR value, needs to be considered. In clay soil, the CBR value of the soil is low, so that stabilization material can be added to its repair. In this study, the stabilization materials used were waste materials in the form of bagasse ash and eggshell powder. Variations in the mixture of bagasse ash mixture used in this study were 7%, 10%, and 13% plus 3% eggshell powder. Testing in this study includes testing moisture content, sieve a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
2
0
0
Order By: Relevance
“…Evidently, the synergistic interaction between ESA and SP demonstrates an even more pronounced capacity for reducing the swelling characteristics inherent in expansive clay. These findings align harmoniously with analogous outcomes in previous studies, as demonstrated by the works of Jain et al [29], Bapiraju and Prasad K [18], Blayi et al [20], and Carlina et al [28].…”
Section: Combined Effect Of Sp and Esasupporting
confidence: 92%
See 1 more Smart Citation
“…Evidently, the synergistic interaction between ESA and SP demonstrates an even more pronounced capacity for reducing the swelling characteristics inherent in expansive clay. These findings align harmoniously with analogous outcomes in previous studies, as demonstrated by the works of Jain et al [29], Bapiraju and Prasad K [18], Blayi et al [20], and Carlina et al [28].…”
Section: Combined Effect Of Sp and Esasupporting
confidence: 92%
“…between these particles increases, culminating in the aggregation or flocculation of clay particles. The cumulative impact translates into a perceptible reduction in the plasticity behavior of the expansive soil, aligning with observations from the previous research[18,[26][27][28]. The progressive decrease in the plasticity index, in tandem with rising ESA content, underscores ESA's propensity to promote clamping, flocculation, and coarsening of the soil particles.…”
supporting
confidence: 85%